Leveraging HIV Programming to Enhance Access to Noncommunicable Disease Care in Southern Botswana. (January 2016) - Reid, Michael J. A.; Haas, Michelle K.; Sedigeng, Pinkie; Ramogola-Masire, Doreen; Friedman, Harvey M.; Ho-Foster, Ari
Objective: The objective of this study was to assess whether HIV programming in southern Botswana could be leveraged to provide care for patients with noncommunicable diseases (NCDs). Methods: A retrospective analysis was performed to determine the spectrum and complexity of NCDs seen by HIV-focused outreach programming delivered between July 2011 and December 2013, to 9 facilities in southern Botswana. The association of HIV status and specific International Classification of Disease codes was examined using bivariate analysis. Results: Outreach HIV physicians recorded 926 outpatient consults involving 835 patients during the studied period. While 25% (n = 209) of patients seen were HIV infected, most patients were either HIV negative (49%, n = 410) or had an unknown HIV status (26%, n = 216). Noncommunicable disease referrals were as common at primary- and district-level facilities (90% [n = 459] versus 93% [n = 301]; P = .22). Conclusion: This study demonstrates how HIV programming in Botswana can be leveraged to improve access to specialist medical services for patients with NCDs.